2013
DOI: 10.1167/iovs.12-11569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drusen Area Detected by Spectral Domain Optical Coherence Tomography and Color Fundus Imaging

Abstract: Citation: Yehoshua Z, Gregori G, Sadda SR, et al. Comparison of drusen area detected by spectral domain optical coherence tomography and color fundus imaging. Invest Ophthalmol Vis Sci. 2013;54;4:24294: -24344: . DOI:10.1167 PURPOSE. To compare the measurements of drusen area from manual segmentation of color fundus photographs with those generated by an automated algorithm designed to detect elevations of the retinal pigment epithelium (RPE) on spectral domain optical coherence tomography (SD-OCT) images. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 30 publications
2
30
2
5
Order By: Relevance
“…15 It is also recognized that subtle changes in microstructural features occur in the early stages of AMD, despite not easily appreciated on clinical examination or on CFPs. 16,17 Such changes can be visualized and quantified on high-resolution imaging modalities such as SD-OCT, including changes to the extent and morphology of drusen, 4,8,9,[18][19][20][21] pigmentary abnoriovs.arvojournals.org j ISSN: 1552-5783 malities, 6 atrophic changes (including nascent GA [nGA] 7,22 and drusen-associated atrophy) and the integrity of the photoreceptor inner-segment ellipsoid (ISe) band. 19 Previous studies have also observed that changes in some of these microstructural features are strongly associated with changes in mesopic microperimetric sensitivity, although it is not possible to conclude whether any of these parameters represent the underlying pathologic changes that are contributing to the decreased visual sensitivity.…”
mentioning
confidence: 99%
“…15 It is also recognized that subtle changes in microstructural features occur in the early stages of AMD, despite not easily appreciated on clinical examination or on CFPs. 16,17 Such changes can be visualized and quantified on high-resolution imaging modalities such as SD-OCT, including changes to the extent and morphology of drusen, 4,8,9,[18][19][20][21] pigmentary abnoriovs.arvojournals.org j ISSN: 1552-5783 malities, 6 atrophic changes (including nascent GA [nGA] 7,22 and drusen-associated atrophy) and the integrity of the photoreceptor inner-segment ellipsoid (ISe) band. 19 Previous studies have also observed that changes in some of these microstructural features are strongly associated with changes in mesopic microperimetric sensitivity, although it is not possible to conclude whether any of these parameters represent the underlying pathologic changes that are contributing to the decreased visual sensitivity.…”
mentioning
confidence: 99%
“…26 Relationships between drusen as defined as yellowish pigmentary changes on color fundus photography and drusen as defined as RPE deformations have been investigated. [27][28][29][30] Good overall correlation between measurements of drusen area using SDOCT important differences between what is captured by the two technologies. Differences in the pointwise agreement between the segmented drusen areas on SDOCT and CFIs are due to the intrinsic differences in how drusen are defined by the two imaging strategies.…”
mentioning
confidence: 99%
“…Several authors have specifically investigated SD-OCT characteristics at the site of visible drusen, including soft drusen by CFP [14,15,[17][18][19][27][28][29]. Khanifar et al demonstrated the existence of a wide variation in drusen morphology by SD-OCT, and differentiated 17 unique drusen patterns.…”
Section: Discussionmentioning
confidence: 99%